Analysis of the MHD Oscillatory Flow and Its Effect on the Temperature and Concentration of Ree-Eyring Fluid Between Two Parallel Horizontal Porous Plates - A. Mohammad AL-Husainy, Sadiq; G. Salih Al-Khafajy, Dheia (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
This work aims to examine the effects of magnetohydrodynamic (MHD) oscillatory flow on heat transfer and concentration in a Ree-Eyring fluid within a channel bounded by two parallel porous plates. The problem is formulated as a nonlinear, nonhomogeneous partial differential equation. The momentum equation is solved using the separation of variables method combined with the perturbation technique to determine the velocity, temperature, and concentration profiles. The obtained solutions are analyzed using MATHEMATICA 14.1, with graphical representations illustrating the results. The analysis is conducted using various parameter values to explore their influence on the system.